MODEL INOVATIF TA’ARUF DIGITAL: STUDI KASUS PADA PROGRAM TA’ARUF SEKOLAH PRANIKAH NURUL ASHRI DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Savvy Dian Faizzati; Ulfatun Wahidatun Nisa (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to analyze the innovative BisaTa’aruf model developed by SPN, evaluate its normative and empirical implementation from the perspective of Islamic family law (fiqh al-munākahāt), and measure its effectiveness in supporting the realization of a harmonious family (sakinah, mawaddah, wa rahmah). The research employs a qualitative design with a normative-empirical approach, using field observations, structured interviews, and secondary data from digital publications and official documentation.The findings reveal three key innovations: (1) the mandatory premarital classes (Kelas Jadi Istri and Kelas Jadi Suami) that equip participants with spiritual, psychological, and financial readiness; (2) the facilitation of digital ta’aruf under the supervision of trained mediators or administrators as third parties; and (3) a flexible nadzar mechanism, conducted either online or offline, within the boundaries of Islamic law. From the perspective of fiqh, this model aligns with the principles of sadd al-dharī‘ah (blocking the means to immorality) and iḥtiyāt (caution), and has proven effective with more than 12,000 ta’aruf processes facilitated and 54 marriages successfully realized.